TAK1 activation of alpha-TAT1 and microtubule hyperacetylation control AKT signaling and cell growth - Nirav Shah (Nature Portfolio, 2018)
Acetylation of microtubules (MT) confers mechanical stability necessary for numerous cellular functions but its regulation is unclear. Here the authors show that the MT acetyltransferase αTAT1 is regulated by TGF-β-activated kinase 1 implicating TGF-β signaling in MT-related functions and disease.